(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
This randomized controlled clinical trial was conducted to assess the efficacy and safety of intralesional triamcinolone acetonide in the treatment of chronic hand eczema comparing with topical clobetasol propionate. A total 60 patients of chronic hand eczema were recruited in the study. Thirty patients (Group A) were treated with intralesional triamcinolone acetonide and the rest 30 (Group B) with topical clobetasol propionate. Severity and improvement were assessed using Hand Eczema Severity Index (HECSI) score. The patients of both groups were followed up at 4th week and 12th week. In Group A, median HECSI score at baseline, 4th week and 12th week were 3, 20 and 20 respectively; whereas these scores were 54, 10 and 8 in Group B. In both groups, HECSI score was decreased gradually but the rate was higher in Group B than Group A (p<0.05). Thinning of skin, an adverse effect, was seen in patients of both the intralesional triamcinolone acetonide (10%) and topical clobetasol propionate (16.7%) groups (p>0.05). The result of this study demonstrates that intralesional triamcinolone acetonide is effective and safe in treating chronic hand eczema but less effective than the topical clobetasol.